Pelatihan Aplikasi GeoGebra pada Materi Persamaan Garis Lurus: GeoGebra Application Training on Straight Line Equations - Zainal Abidin; Eni Susanti; Surya Sari Faradiba; Sunismi Sunismi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Diverse and effective learning media will improve learning achievement. One of the alternatives is the GeoGebra application. The objectives of this community service activity include: Introducing GeoGebra applications to students; improve students' ability to solve straight-line equation problems. The implementation method for this training consisted of three stages followed by class VIII students at SMP Diponegoro Junrejo Batu. The first stage is pre-activity, carried out by observation and interviews with subject teachers and coordinating the service team with the school. The second stage is the implementation of the activity: the implementation of the activity begins with the distribution of questionnaires to students about the initial understanding of the GeoGebra application, then the presentation of the GeoGebra application material and demonstration of use in solving straight-line equation problems and direct practice assignments using the GeoGebra application. The practice of operating the GeoGebra application was carried out in two meetings. The third stage is monitoring and evaluation. Monitoring is carried out by looking at the results of students' work in solving the problems given. Evaluation is in the form of assessing the results of the participants' work in solving straight-line equation problems. This training activity showed that 73% of the participants, or 23 of the 31 participants, could operate the GeoGebra application to solve straight-line equation problems.